KALANDUE ANADARA GRANDIS SEA SHELLS AS ECO-FRIENDLY FLOOR FINISH MATERIALS - Muhammad Zakaria Umar; Asri Andrias Herman Balo; Hudi Sonta; Nurdin Takdir (Universitas Mercu Buana, 2019)
A high low energy in buildings is determined in the potential use of materials. Tile material is potentially made by architects as a sustainable building material. The use of tiles was marginalized by ceramic flooring products produced by large industries. The result of studies on the issue of global warming note that the embodied CO2 from the tile floor is almost seven times more than the embodies CO2 tiles. This result shows that tile products are environmentally sound and sustainable compared to tile floors. In another side, Kendari City is a Coastal City, and there are Kampung KB (Family Planning) that much mothers in this village busy every day with searching metti-metti/kalandue (Anadara grandis). During this time, shell kalandue fisherman catches only utilized meat/adductor muscle, while the shell is removed and uses as waste. In order for the tile to be competitive and interesting to be used as the floor of the house, it is necessary to study to create a tandem-based kalandue. This research is intended to create a tandem-based kalandue that used exploration method. The process of analysis is done qualitatively, so it gets the form of a tile. The shape of the tiles is transformed from the parameters to the resulting tandem-based kalandue shell. This study concluded that kalandue sea shells as eco-friendly floor finish material made, as follows: the working tools used were simple and sufficient. The working materials used are quite available and economical. The making process is done quickly and easily.